Influence of Phosphorus Microalloying on Molidification， Hot Deformation and Mechanical Properties in Nickel/Nickel Iron-based Alloys - Wang Changshuai, Wu Yunsheng, Wu Hao, Zhao Yong, Pei Yubing, Wang Tianjian, Jiang Lei, Xu Ziyu, Nie Liping, Gao Zhenhuan, Gong Xiufang, Zhou Lanzhang (Teshugang)
Nickel/nickel iron-based alloys are widely used in the manufacturing of hot end components for aircraft engines， gas turbines， advanced ultra-supercritical power plants， and other equipment due to their excellent oxidation resistance/corrosion resistance and high-temperature mechanical properties. Phosphorus （P） microalloying is one of the effective ways to improve their high-temperature creep strength and increase creep fracture life while maintaining the same main elements contents. P has extremely low solubility and low activity in nickel/nickel iron-based alloys. During solidification process， it is easy to accumulate at the front of the solid/liquid interface and is difficult to form compounds. By affecting the solidification and thermal deformation behavior， it changes the microstructural characteristics and thus affects the final mechanical properties. This article summarizes the distribution characteristics of phosphorus during the solidification process and its impact on solute segregation and solidification microstructure， the influence of solidification microstructure changes on subsequent thermal deformation behavior， the phosphorus segregation behavior during heat treatment and aging processes and its effect on microstructure， the influence mechanism of phosphorus segregation characteristics and microstructure changes on mechanical properties and deformation mechanisms. The results show that P tends to become enriched at the solid/liquid interface front during solidification， thereby promoting element segregation. After heat treatment， P segregates at grain boundaries or phase interfaces， optimizing the morphology of grain boundary precipitates and enhancing grain boundary strength. The influence of P on the hot deformation behavior arises from the dual effects of solute drag by phosphorus atoms and the promotion of recrystallization nucleation by MC carbides. The influence of P on the hor deformation behavior is related to the state of alloy. The appropriate P content can improve the creep rupture strength of alloys； however， this beneficial effect is constrained by both the alloy system and the magnitude of creep stress. Based on the results mentioned above， this paper established the influence mechanism of P in the entire process of casting， forging， and component performance. It also briefly introduces the current problems and further research directions.